Influence of Brand Loyalty and Perceived Quality Analysis on Consumer Purchase Decisions - Muhammad Hery Santoso; Jefri Putri Nugraha; Nawiyah Nawiyah; Etty Zuliawati Zed; Miska Irani Tarigan (PT Mattawang Mediatama Solution, 2023)
The purpose of this research is to analyze the effect of brand loyalty and perceived quality on consumer purchasing decisions. The research design used in this study uses a quantitative associative method. Based on the results of data analysis that has been carried out in the first hypothesis (H1), which states that brand loyalty has a positive and significant effect on consumer purchasing decisions, the t-count value of 8,197 is greater than the t-table value, which is 1,666, testing the second hypothesis (H2), which states that perceived quality has a positive and significant effect on consumer purchasing decisions obtained by a t-count value of 10,769 greater than the t-table value of 1,666, which means that brand loyalty and perceived quality have a positive and significant effect on consumer purchasing decisions, while the R-square value is obtained by 0.616 which states that brand loyalty and perceived quality variables influence consumer purchasing decisions by 61.60% and the remaining 38.40% are influenced by other variables.